Performance-related pay-hype versus reality - With special reference to public sector organizations - Agrawal, Chetan (2012)
Performance-related pay has been regarded as the sole crusader for obtaining effective performance by several academicians and professionals. However, contrary to this popular belief, research shows that performance-related pay is not effective in all institutional settings. This article discusses that reward bargains need to be customized according to the institutional structure, thus discarding the notion that only performance-related pay can improve performance. Characteristics of the public sector (organizational structure, personnel management systems, nature of resources and incentives, multiple principals, measurement problems and intrinsic motivation) which are not in sync with performance-regular related pay are also discussed in order to exemplify that performance-related pay instead of improving performance creates barriers. Pitfalls of performance-related pay (intrinsic motivation, decreased cooperation, decreased equity and higher control) are discussed in order to suggest that these pitfalls should be considered before performance-related pay systems are adopted by the organization. Examples from British and French civil services are used throughout the article in order to further clarify the issues. - Reproduced.
Keywords: Motivation; Performance appraisal; Wages